INVESTMENT FOR A SPECIFIC PURPOSE WITH LONG TERM SAVING AND INVESTMENT: A CASE OF INVESTMENTS FOR CHILDREN - Reddy, Renati Jayaprakash; Shambhavi B. R. (International Journal of Research -GRANTHAALAYAH, 2025)
Rising education costs and growing economic uncertainty have increased the need for systematic financial planning for children’s education. This study examines parents’ investment behaviour toward children-specific investment plans, focusing on the influence of demographic variables on the selection of investment avenues and evaluation of investment attributes. The study is based on primary data collected from 449 middle-income parents in Bangalore using a stratified sampling technique. Discriminant analysis is applied to assess the effects of age, gender, income, and savings on investment decisions, and the reliability of the research instrument is found to be acceptable. The findings reveal that age does not significantly influence either the choice of child investment plans or the assessment of investment attributes. Gender does not affect the selection of investment avenues but significantly influences perceptions of investment attributes such as investment period, fund safety, credit rating, and adequacy of funds at the time of need. Income and savings emerge as the most significant determinants, affecting both the selection of investment instruments and the evaluation of their features. The study concludes that parents prioritize long-term investment horizons, fund security, and timely availability of funds when planning for children’s education. The findings offer practical insights for financial institutions in designing effective and flexible child-focused investment products.